2013
DOI: 10.1080/10408398.2010.526725
|View full text |Cite
|
Sign up to set email alerts
|

Avena sativa(Oat), A Potential Neutraceutical and Therapeutic Agent: An Overview

Abstract: The aim of the present review article is to summarize the available information related to the availability, production, chemical composition, pharmacological activity, and traditional uses of Avena sativa to highlight its potential to contribute to human health. Oats are now cultivated worldwide and form an important dietary staple for the people in number of countries. Several varieties of oats are available. It is a rich source of protein, contains a number of important minerals, lipids, β-glucan, a mixed-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
200
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(229 citation statements)
references
References 116 publications
4
200
0
8
Order By: Relevance
“…Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013). Another study has indicated that the consumption of oats and oats bran may reduce the risk of colon cancer not only because of their high fiber contents but also due to AVAs (Guo et al 2010).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013). Another study has indicated that the consumption of oats and oats bran may reduce the risk of colon cancer not only because of their high fiber contents but also due to AVAs (Guo et al 2010).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
“…The AVAs differ in the antioxidant activity, AVA-C having the highest activity, followed by AVA-B and AVA-A (Peterson et al 2002;Ji et al 2003). They are reported to be stopping the oxidation of lipid and linoleic acid in foods (Fagerlund et al 2009;Singh et al 2013). Fagerlund et al (2009) found that, compared with α-tocopherol, AVAs protected linoleic acid from oxidation initially to a smaller extent initially.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
See 3 more Smart Citations